"Back‐to‐Front" Type Synthesis of Polyfunctionalized Indazoles: Nitromethane Mediated, Domino Benzannulation of o‐Chloropyrazolyl Ynones. Issue 11 (31st March 2021) - Beesu, Mallesh; Mehta, Goverdhan
Abstract: A one‐pot domino benzannulation protocol involving strapping of o‐chloropyrazolyl ynones with various nitromethane derivatives has been devised as a entry to diversely functionalized indazole frameworks. These preparatively useful transformations proceed via tandem Michael addition‐intramolecular SN Ar reaction pathway to efficiently furnish a range of functionally enriched indazoles with bioactivity potential from readily accessible precursors. Abstract :